Relationships between psychopathology, psychological process variables, and sociodemographic variables and comparison of quarantined and non-quarantined groups of Malaysian university students in the COVID-19 pandemic - Nicholas Tze Ping Pang; Sandi James; Nelbon Giloi; Syed Sharizman Syed Abdul Rahim; Azizan Omar; Mohammad Saffree Jeffree; Firdaus Hayati; Mei, Ching Lim; Mohd Amiruddin Mohd Kassim; Jun, Rong Ng (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The COVID-19 pandemic has had considerable psychological health impacts across the globe. This study aimed to establish the psychological process variables underlying psychopathology in Malaysian public university students during the national Movement Control Order (MCO). The aim was to craft structured and sustainable psychological support programs with these students. We conducted a cross-sectional study involving Malaysian university students subjected to the Malaysian MCO. Structured questionnaires measuring sociodemographic factors, measures of depression, anxiety, stress, psychological mindedness, psychological flexibility and state mindfulness were employed. A total of 515 students participated in this study with 12 students (2.3%) being quarantined at the time. Many of them scored ‘moderate’ or above on the Depression, Anxiety and Stress Scale (DASS) with 20.2%, 25.0% and 14.2%, respectively. Quarantined students had higher depressive symptoms, with female students scoring significantly higher for depression, anxiety, and stress. Multiple regressions suggested gender and quarantine status predicted depression scores. However, only gender significantly predicted anxiety and stress. Psychological flexibility and psychological mindedness (Insight subscale) are significantly correlated with depression, anxiety, and stress, with psychological mindedness predicting all three psychopathologies. This study demonstrates that gender, psychological flexibility, and psychological mindedness are key demographic and psychological factors impacting students. Targeting psychological flexibility and psychological mindedness may enable timely prevention and intervention programs for our students to support their mental and physical health as we move through, and out of, the pandemic.